IDENTIFIKASI KERUSAKAN EKOSISTEM MANGROVE DI KELURAHAN BIRA KOTA MAKASSAR - Andi Muhammad Akram; Hasnidar Hasnidar (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2022)
Mangrove ecosystems are one of the most important areas in maintaining the level of diversity of organisms in the sea. Mangrove damage is caused by abrasion, lack of heeding of the carrying capacity of the coastal environment, and lack of knowledge and awareness of the community around the coast about mangrove ecosystems ecologically / economically. This research was conducted in January – March 2021 in Bira Village, Tamalanrea District, Makassar City, South Sulawesi Province.This study aims to determine the level of mangrove damage, find out damage factors and calculate the estimated value of mangrove ecosystem damage claims in Bira Village, Makassar City. This research used a survey or direct observation method. The results showed that mangrove vegetation in Bira Village is low with very little species diversity. The level of mangrove forest destruction is still in the good category with a percentage of 30.89%. The causative factors are due to the felling of mangrove trees for fuel, infrastructure development, and coastal abrasion. Based on rehabilitation costs referring to P.8 / KSDAAE / SET / REN.2 / 10/201 concerning Activity Standards and Costs for Conservation of Natural Resources and Ecosystems in 2018, a total rehabiliation cost of Rp. 350,220,000 was obtained with a total mangrove forest area of 10 Ha.